2015
DOI: 10.1182/blood.v126.23.515.515
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Open-Label Pilot Study to Evaluate the Hematopoietic Stem Cell Mobilization of TG-0054 Combined with G-CSF in 12 Patients with Multiple Myeloma, Non-Hodgkin Lymphoma or Hodgkin Lymphoma - an Interim Analysis

Abstract: Background: TG-0054 (burixafor) is a potent and selective antagonist of human chemokine receptor CXCR4 that inhibits the binding of stromal-derived factor 1 (SDF-1). Interruption of the CXCR4/SDF-1 interaction prevents sequestration of CD34+ stem cells to the bone marrow and subsequently mobilizes these cells into the peripheral blood within 1 to 3 hours of drug administration. Materials and Methods: An open-label, phase II pilot trial was conducted in patients with multiple myeloma (MM), non-Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The fluorescence-based antibody competition assay allows for a rapid and quantitative determination of the half-maximal inhibitory concentration (IC 50 ) and the inhibitory constants (K i ) for each CXCR4 ligand analyzed, allowing a direct comparison of pharmacological parameters. The lowest K i (~ 0.1 nM) was observed for Burixafor (TG-0054), an orally bioavailable stem cell mobilizing agent currently in phase I trials 23 , followed by IT1t (K i ~ 0.6 nM), an allosteric inhibitor that is currently not in clinical development. AMD3100, the only marketed CXCR4 antagonist approved to mobilize hematopoietic stem cells in cancer patients 62 and currently also in advanced clinical trials for therapy of other CXCR4-associated diseases, showed a high nanomolar K i with 221 nM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence-based antibody competition assay allows for a rapid and quantitative determination of the half-maximal inhibitory concentration (IC 50 ) and the inhibitory constants (K i ) for each CXCR4 ligand analyzed, allowing a direct comparison of pharmacological parameters. The lowest K i (~ 0.1 nM) was observed for Burixafor (TG-0054), an orally bioavailable stem cell mobilizing agent currently in phase I trials 23 , followed by IT1t (K i ~ 0.6 nM), an allosteric inhibitor that is currently not in clinical development. AMD3100, the only marketed CXCR4 antagonist approved to mobilize hematopoietic stem cells in cancer patients 62 and currently also in advanced clinical trials for therapy of other CXCR4-associated diseases, showed a high nanomolar K i with 221 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Another orally available small molecule is MSX-122 that was described as a partial antagonist of CXCR4 and is currently investigated in a phase II clinical trial as an oral drug for hot flashes in breast cancer-positive post-menopausal women 20 , 22 . Two other orally available small drug candidates are Burixafor (TG-0054) that is a monocyclic CXCR4 antagonist und currently tested in a phase II study for stem cell mobilization 20 , 23 , and the isothiourea compound IT1t that was used for crystallization of the CXCR4 receptor thereby revealing a distinct binding mode from AMD3100 within the receptor binding pocket 24 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Examining these varied studies, an extension of plerixafor indications is to be expected in the coming years, as are new pharmacological alternatives. Indeed, new compounds targeting CXCR4 are in development: small molecules (TG-0054 [60,61,62]) such as plerixafor, but also peptides (BL-8040 [63], (BK)T140 [64], POL6326 [65], LY2510924 [66]), or oligonucleotides (NOX-A12 [67]). All have already been tested in humans as part of phase I or early phase II clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence-based antibody competition assay allows for a rapid and quantitative determination of the half-maximal inhibitory concentration (IC50) and the inhibitory constants (Ki) for each CXCR4 ligand analyzed, allowing a direct comparison of pharmacological parameters. The lowest Ki, (~ 0.1 nM) was observed for Burixafor (TG-0054), an orally bioavailable stem cell mobilizing agent currently in phase I trials 23 , followed by IT1t (Ki ~ 0.6 nM), an allosteric inhibitor that is currently not in clinical development. AMD3100, the only marketed CXCR4 antagonist approved to mobilize hematopoietic stem cells in cancer patients 60 and currently also in advanced clinical trials for therapy of other CXCR4associated diseases, showed a high nanomolar Ki with 221 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Another orally available small molecule is MSX-122 that was described as a partial antagonist of CXCR4 and is currently investigated in a phase II clinical trial as an oral drug for hot flashes in breast cancer-positive post-menopausal women 20,21 . Two other orally available small drug candidates are Burixafor (TG-0054) that is a monocyclic CXCR4 antagonist und currently tested in a phase II study for stem cell mobilization 23,21 , and the isothiourea compound IT1t that was used for crystallization of the CXCR4 receptor thereby revealing a distinct binding mode from AMD3100 within the receptor binding pocket 24,25,26 . Besides small molecules, several peptide-based CXCR4 antagonist are also being tested for multiple applications.…”
Section: Introductionmentioning
confidence: 99%